Internal Capital Markets and Corporate Refocusing - Matsusaka, John G.; Nanda, Vikram (Journal of Financial Intermediation, 2002)
This paper develops a theory of organization based on the benefits and costs of internal capital markets. A central assumption is that the transaction cost of raising external funds is greater than the cost of internal funds. The benefit of internal resource allocation is that it gives the firm a real option to avoid external capital markets (and the associated deadweight transaction costs) in more states of the world than single-business firms. The cost is that internal resource flexibility exacerbates an overinvestment agency problem. The optimal focus is determined by trading off the benefit of the option against the cost of overinvestment. In this context, we show how the relative efficiency of integration and separation depends ultimately on assignment of control rights over cash flow. Testable implications are derived for the level of divisional investment, the sensitivity of divisional investment to cash flow, and the diversification discount. Journal of Economic Literature Classification Numbers: D82, G34, L22.